Investment banking : institutions, politics, and law - Morrison, Alan.; Wilhelm, William J. (Oxford ; New York : Oxford University Press, 2007)
This book provides an economic rationale for the dominant role of investment banks in the capital markets, and uses it to explain both the historical evolution of the investment banking industry and also recent changes to its organization.
Includes index.
Includes bibliographical references: p. (311-331).
rpm 20/09/2016, ijb 14/03/2019
Loan
Keywords: Investment banking; Investment banking -- History; Investment; Banks and banking